Schumpeter | Unlocking Keyence's secret. (Economist, 2022)
The article offers business news briefs. Explanations of Keyence's remarkable run usually start with its focus on its clients. People who have witnessed up close the relationship between the company's engineers and those who employ their services describe a painstaking process of optimization. Without Keyence's engineers to ensure that all possible efficiencies are eked out, factories risk a bit more downtime.